Evangelizacija svetih bratov Cirila in Metoda - izziv za pastoralno delo tudi danes? - Šegula, Andrej (Edinost in dialog, 2013)
The basis of the article is the fact that the task of pastoral care is to reach people, as much the individual as the society as a whole. The goal always remains the same - the annunciation of the Gospel, the search for the contact with God, and the desire to serve the fallow man. In this context we want to discover the life context of the great Slavic apostles Cyril and Methodius. Their life story reveals many elements of innovative pastoral work. All these have been illustrated by guidelines of the Second Vatican Council, with the emphasis on %aggiornamento% (placement into the circumstances of today), the restoration of the Church here and now, and on the search of the dialogue with the world (dialogue does not mean adjustment at any cause). In the last part of the article several common points are highlighted: pastoral planning, the strive for new Evangelisation, place and meaning of the dialogue in the search for compromises, and the meaning of education in the time of saints Cyril and Methodius and today. Especially important is the preparation of priests for their mission since it is them who are the first carriers of pastoral restoration.
Keywords: Catholic Church; Cyrillus; evangelizacija; katoliška cerkev; Methodius; pastoralno delo; svetniki; Vatikanski koncil II.